Anisotropic distribution of alpha particles in a tokamak reactor - Youjun Hu; Xingyuan Xu; Yingfeng Xu; Yifeng Zheng; Guoqiang Li; Zhiyong Qiu; Youwen Sun (Nuclear Fusion)
We carried out systematic study of neoclassical equilibrium distribution of α particles born from deuterium–tritium nuclear fusion in a tokamak reactor. The distribution in the phase space is visualized in various 2D planes. We studied a previously known but less investigated phenomenon—the co-current flow of α particles. We gave detailed explanation for this flow by examining the collisionless evolution of toroidal filament sources, using both the guiding-center drift model and full orbit model. We found that the flow appears because of the co-count asymmetry, which makes co-going α particles on average stay in weaker magnetic field region than that of the counter-going ones.